Cervical spine injuries sustained by motorcyclists in road crashes in Malaysia - Ooi, Soo Shen; Wong, Shaw Voon; Radin Sohadi, Radin Umar; Abdul Aziz, Azhar; Megat Ahmad, Megat Mohamad Hamdan (Woodhead Publishing, 2005)
This study looks at cervical spine injuries sustained by motorcyclists in motorcycle road crashes. The motorcyclist is relatively more exposed to road hazards compared to the protected car passenger. They are therefore more prone to injury than those traveling in any other form of transportation. The motorcycle is relatively less stable and accords little protection to passengers in road crashes compared to a four-wheeled vehicle. The cause of injury and injury mechanisms are more uncertain for a motorcyclist compared to a car driver. The objective of the present study is to correlate the motorcycle crash mode to the cervical injury sustained by motorcyclists in real-world scenes. Motorcyclists with cervical injuries admitted to the hospitals were selected for investigation. The types of injuries sustained were acquired from medical reports. Information on the crash scene and crash mode was obtained from police reports and interview sessions arranged with the motorcyclists involved in the crash. Generally, a high count was noted for injuries to the lower cervical vertebrae, especially at vertebrae C5, intervertebral C5-C6, and vertebrae C6. The upper cervical spine was observed to have a high frequency of injury at C2, especially the odontoid process. Statistical analysis reveals that the vehicle crash mode is significant in determining the cervical injury mechanism sustained by motorcyclists (p < 0.05), and thus basic injury types sustained. Neck flexion and extension movements are the most frequent neck injury mechanisms, especially in frontal and rear end impacted motorcycles. Burst fractures were commonly observed in frontal impacts, while side impact and skidding motorcyclists were found to have a high frequency of uncinate process fractures, a result of neck lateral flexion. At the end of the study, a logistic regression model was developed. The model is simple and may be referred by paramedics in making any prompt prediction related to neck injury of motorcyclist due to road crash.